Stereotactic Body Radiotherapy for Spinal Metastases: What are the Risks and How Do We Minimize Them?. (15th October 2016) - Chang, Joe H.; Shin, John H.; Yamada, Yoshiya J.; Mesfin, Addisu; Fehlings, Michael G.; Rhines, Laurence D.; Sahgal, Arjun
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Systematic literature review. Objectives: To summarize the risks of 3 key complications of stereotactic body radiotherapy (SBRT) for spinal metastases, that is, radiation myelopathy (RM), vertebral compression fracture (VCF), and epidural disease progression, and to discuss strategies for minimizing them. Summary of Background Data: RM, VCF and epidural disease progression are now recognized as important risks following SBRT for spine metastases. It is unclear at this stage exactly how large these risks are and what strategies can be employed to minimize these risks. Methods: A systematic review of the literature using MEDLINE and a review of the bibliographies of reviewed articles on SBRT for spinal metastases were conducted. Results: The initial literature search revealed a total of 376 articles, of which 38 were pertinent to the study objectives. The risk of RM following SBRT was found to be dependent on the maximum dose to the spinal cord and estimated to be ≤5% if the recommended published thecal sac dose constraints are adhered to. The crude risk of VCF was 13.7% (range: 0.7%–40.5%), and, on average, 45% were surgically salvaged. It has been shown that the risk of VCF is dependent on several anatomic and tumor-related factors including the SBRT dose per fraction. The crude risk of local failure at 1 year was 21.4% (range: 12%–27%) of which 67% (range: 38%–96%) occurred within the epidural space. The grade of epidural disease has been shown to be associated with the risk of local failure. Conclusion: The risk of RM after spinal SBRT is low in particular if recommended dose metrics are adhered to. There is a significant risk of both VCF and epidural disease progression after spinal SBRT. These risks can potentially be minimized by identifying the risk factors for these complications, and performing careful radiotherapy and surgical planning. Level of Evidence: 2